Living with migraine: A meta-synthesis of qualitative studies - Battista, Simone; Lazzaretti, Arianna; Coppola, Ilaria; Falsiroli Maistrello, Luca; Rania, Nadia; Testa, Marco (Frontiers in Psychology, 2023)
Introduction: Migraine is one of the top ten causes of disability worldwide. However, migraine is still underrated in society, and the quality of care for this disease is scant. Qualitative research allows for giving voice to people and understanding the impact of their disease through their experience of it. This study aims at synthesising the state of the art of qualitative studies focussed on how people with migraine experience their life and pathology. Methods: MEDLINE via PubMed, EMBASE, CINAHL, PsycINFO and Cochrane Library were consulted up to November 2021 for qualitative studies. Studies to be eligible had to focus on young adults (age > 18 years) with a diagnosis of primary episodic or chronic migraine following the International Classification of Headache. The quality of the study was analysed using the CASP (Critical Appraisal Skills Programme) tool. The synthesis was done through a thematic analysis. CERQual (Confidence in Evidence from Reviews of Qualitative research) approach was used to assess the confidence in retrieved evidence. Results: Ten studies were included, counting 262 people with migraine. Our synthesis produced four main themes. 1) ‘Negative impact of migraine symptoms on overall life’ as migraine negatively impacts people’s whole life. 2) ‘Impact of migraine on family, work and social relationship’ as migraine reduces the possibility to focus at work and interact with people. 3) ‘Impact of migraine on emotional health’ as people with migraine experience psychological distress. 4) ‘Coping strategies to deal with migraine’ such as keep on living one’s own life, no matter the symptoms. Conclusions: Migraine negatively impacts people’s whole life, from private to social and work sphere. People with migraine feel stigmatised as others struggle with understanding their condition. Hence, it is necessary to improve awareness among society of this disabling condition, and the quality of care of these people, tackling this disease from a social and health-policy point of view.